Host signature effect on plant root‐associated microbiomes revealed through analyses of resident vs. active communities. (21st August 2013) - Ofek, Maya; Voronov‐Goldman, Milana; Hadar, Yitzhak; Minz, Dror
Summary Plant roots create specific microbial habitat in the soil – the rhizosphere. In this study, we characterized the rhizosphere microbiome of four host plant species to get insight into the impact of the host (host signature effect) on resident vs. active communities. Results show a distinct plant host specific signature found among wheat, maize, tomato and cucumber, based on the following three parameters: (i) each plant promoted the activity of a unique suite of soil bacterial populations; (ii) significant variations were observed in the number and the degree of dominance of active populations; and (iii) the level of contribution of active (rRNA‐based) populations to the resident (DNA‐based) community profiles. In the rhizoplane of all four plants, a significant reduction of diversity was observed, relative to the bulk soil. Moreover, an increase in DNA–RNA correspondence indicated higher representation of active bacterial populations in the residing rhizoplane community. This study demonstrates that the host plant determines the bacterial community composition in its immediate vicinity, especially with respect to the active populations.